Klick Health : global pandemic crisis management - White, Jennifer, active 2023; Licholai, Gregory P., 1964- (London : Yale School of Management, 2021)
The largest private health marketing company in the world, Klick Health, is led by Lori Grant. She and Leerom Segal, the CEO of Klick, listened to news reports about a mysterious illness that was killing hundreds of people in Wuhan, China. In a matter of hours, they produced a nine-point safety protocol and business continuity plan. The Toronto headquarters as well as the Philadelphia and New York locations of Klick Health were shut down. Within days, all workers were returned to their bases of operations in Toronto or New York. After the COVID-19 epidemic, Klick Health released its nine-point safety policy.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Crisis management -- China; COVID-19 Pandemic, 2020- -- China